Analysis of Fatty Acids, Phenolic Compounds, Antimicrobial Activity, Paper Chromatography, and Metal and Mineral Content of the Arbutus pavarii Plant - Hamad Hasan; Aish Ali; Nevein Abdel-Hady (AlQalam Journal of Medical and Applied Sciences, 2025)
The contents of fatty acids, phenolic acids, minerals, and some metals, as well as antibacterial activities, were studied in leaf and fruit samples collected from the Al Gabal Al Alakhder area. Different instruments were used in this study. The GC-MS was employed to determine the types and contents of fatty acids and phenolic acids. Atomic absorption spectroscopy was used to measure the concentrations of heavy metals, while the flame photometer was used to estimate the concentrations of potassium, sodium, and calcium. also, the spectrophotometer was applied to measure the contents of phosphorus. The antibacterial activities were carried out on different bacterial species, including positive and Gram-negative bacteria such as Staphylococcus aureus, Bacillus subtillus, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, and Salmonella typhimurium. The results of this study recorded the presence of different types and contents of phenolic acids, including The Phenolic acids content in the studied plant leaves and fruits of Arbutus pavarii were ranged as follows: Arbutus pavarii leaves: Chlorogenic acid (0.0179 mg/g), 3,4-Dicaffeoylquinic acid (0.1022mg/g), 3,5-Dicaffeoylquinic acid (0.1325 mg/g), and 4,5-Dicaffeoylquinic acid (0.0205 mg/g). For the Arbutus pavarii fruits: Chlorogeneic acid (0. .0000026 mg/g), 3,4-Dicaffeoly guinic acid (0.00344 mg/g), 3,5-Dicaffeoly guinic acid (0.00572mg/g), 4,5-Dicaffeoly guinic acid (0.00419mg/g), 2,5-dihydroxy Benzoic acid (0.00000365mg/g), Cinnamic acid (0.00000696 mg/g), Galic acid (0.000014 mg/g) and Geraniol (0.00000314 mg/g). On the other side, the concentrations of fatty acids were the concentrations of Saturated fatty acids in A.pavarii leaves and fruits as follows (0.079 and 0.153 mg/g) respectively. Concentration of unsaturated fatty acid in A.pavarii leaves and fruits as follows: Monounsaturated fatty acid (0.065 and 0.000 mg/g), respectively. Polyunsaturated fatty acid (0.034 and 0.000 mg/g), respectively. The concentration of saturated fatty acids in leaves and fruits of Arbutus pavarii is as follows: Arbutus pavarii leaves, Hexadecanoic 0.034 mg/g and Octadecanoic (0.045 mg/g). Arbutus pavarii fruits: Butanoic (0.003mg/g), Octanoic (0.007mg/g), Decanoic (0.005mg/g), Tridecanoic (0.073mg/g), and Pentadecanoic (0.011mg/g). The antibacterial activity against the selected bacterial species showed high efficiency of the Arbutus pavarii plant extract in the inhibition of most species.